UPAYA PENINGKATAN PENGHASILAN TAMBAHAN HOME INDUSTRI JENANG CIKRU SEBAGAI PENDIDIKAN BERBASIS PELESTARIAN KEARIFAN LOKAL DI DESA BANYUBIRU, KECAMATAN BANYUBIRU, KABUPATEN SEMARANG, PROVINSI JAWA TENGAH - Nila Kusumaningtyas, Ismatul Khasanah, Ari Widyaningrum, (UNIVERSITAS SLAMET RIYADI, 2019)
Banyubiru village is located around the Rawa Pening area, where there are many water plants such as swamp lotus that thrives in this area. Lotus has many benefits and potential that can be processed for the welfare of the Banyubiru community. As one of the results of processing from lotus flower seeds which become Banyubiru's special culinary, namely jenang cikru which is a pearl of local wisdom that needs to be preserved and regenerated. There were several vocations targeted at the service location, one of which was home industry-based vocational. Home industry-based vocational training was prepared for the target of selling women, and vocational training based on swamp lotus cultivation as the main ingredient in making jenang cikru was prepared for all residents. The focus of the program is to increase the income of members of the Mitra Family through a superior program to develop the Jenang Cikru home industry. Formation of program clusters which includes: (1). The cluster of swamp lotus cultivation and the process of making Jenang Cikru, (2). The marketing cluster results are synergistic and integrated to produce swamp lotus cultivation and processing of jenang. Continuous guarantee programs are carried out through the development of cooperation with various elements of society, academics, stakeholders, and industry. The conclusion of this service activity is traditional culinary preservation which is the hallmark of Banyubiru Village so that it can improve and lift the economy of the home industry in jenang cikru.Â Key words: Home, Industry, Jenang Cikru.